Integrating indigenous learning through an ethnopedagogical perspective in elementary schools: A systematic literature review - Hikmah Syafiulia, Sabila; Mahendra Wasita Aji, Styo; Salsabiltisa De Side, Joeang (EduStream: Jurnal Pendidikan Dasar, 2025)
Indonesia possesses a rich diversity of cultures and local knowledge that can significantly enrich educational practices in elementary schools. However, these local values are often overlooked in formal education, despite their potential to strengthen cultural identity and promote social justice. This study aims to explore the definition, impact, and research gaps related to Indigenous Learning (IL) within the context of ethnopedagogy in elementary education. The method employed is a Systematic Literature Review (SLR) guided by PRISMA, based on an analysis of 18 Scopus-indexed articles published between 2021 and 2025. The results indicate that IL promotes social learning, community participation, and inclusive educational practices that enhance students’ academic outcomes and preserve cultural authenticity. Furthermore, the study finds that the role of local leadership in the education system needs to be further investigated to support culturally responsive education. Thus, IL offers valuable insights for elementary school educators in implementing inclusive teaching approaches and in strengthening students’ resilience and cultural identity. In conclusion, the integration of local wisdom-based learning through an ethnopedagogical perspective is highly relevant and strategic for building elementary education that is culturally rooted, socially just, and adaptive to future challenges.